PENGARUH PERSONALITY TRAITS TERHADAP HEDONIC MOTIVATION, UTILITARIAN MOTIVATION, SEARCH INTENTION, DAN PURCHASE INTENTION PADA PENGUNJUNG SITUS ONLINE DI INTERNET - ADRIAND, . (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
The purpose of this study is to explain the influence of personality traits on hedonic and utilitarian motivation, to explain the influence of hedonic motivation on search intention, to explain the effect of utilitarian motivation on search intention, moreover to explain the effect of search intention on purchase intention. The object of this study focuses on the internet visitors. The number of samples is 146 respondents. The data analysis technique which is used in this study is structural equation model using Lisrel program. The findings in this study suggest that personality traits gives positive effect on hedonic motivation, also personality traits gives positive effect on utilitarian motivation, while hedonic motivation gives negative effect on search intention, utilitarian motivation gives positive effect on search intention, and search intention gives positive effect on purchase intention of the internet visitors.